House price indices using assessed values statistics - Shi, Song (International Journal of Strategic Property Management, 2015)
This paper investigates tax inequities in assessed values and how these inequities in tax assessments affect house price indices using assessed values statistics. Using the unique rating valuation data from the top 10 cities of New Zealand during the period 1994–2009, it finds that house price measurements using the Sale Price Appraisal Ratio (SPAR) method have performed well compared to the repeated sales method suggested by Case and Shiller (1989) and the assessed values (AV) method proposed by Clapp and Giaccotto (1992). The presence of systematic estimated errors (both vertical and horizontal inequities) in assessed values posts a concern for house price measurements using assessed values statistics. In this situation, both the SPAR and AVmethods benefit from the law of compensation of errors by using all transaction data. A policy implication is that the SPAR model is a good choice when using assessed values to measure house price movements at frequent time intervals, in particular for small countries.First Publish Online: 1 Apr 2015